Nursing and midwifery workforce and the new Sustainable Development Goals (2016-2030) - Mamede, Marli Villela (Rev Rene, 2018)
In September 2015, the (United Nations) UN member countries approved the Global Plan for Sustainable Development with the purpose of enhancing economic, social and environmental indicators for the next generations. This plan is the result of a process started in Brazil, in 2012, during the Rio + 20 Conference, which followed a wide consultation system to ensure diversified perspectives and experiences in the composition of the Post-2015 Agenda. The new agenda titled “Transforming Our World: The 2030 Agenda for Sustainable Development” consists of a Declaration with 17 Objectives and 169 goals intended to guide the actions of the international community in the following years (2016-2030), thereby helping countries to achieve sustainable development.